Reconstructed paleo-oxygen concentration, stable isotope measurements and Gaussian interpolated Δδ13C obtained from the IODP Site 339-U1385 for the past 1.5 Ma, including trace element analyses and Uvigerina spp. abundance over MIS 27-21 - Nicola C Thomas; Harold J Bradbury; David A Hodell (PANGAEA, 2022)
The dataset compiles reconstructed changes in deep-water oxygen concentration for the past 1.5 Ma using stable carbon isotope measurements of benthic foraminifer: the epibenthic Cibicidoidies wuellerstorfi and the infaunal Globobulimina affinis, obtained from the International Ocean Discovery Program (IODP) Site 339-U1385 along the Iberian Margin (Northeast Atlantic; 2578 mbsl). The dataset covers the Middle Pleistocene Transition (MPT) and has a mean sampling frequency of ~290 yrs. Changes in North Atlantic deep-water oxygenation for the past 1.5 Ma reveal a significant (>40 μmol/kg) reduction in glacial deep-water oxygen concentration at ~960 ka suggesting increased storage of respired carbon, which is consistent with a drawdown of glacial atmospheric pCO2 values. The dataset includes the following records obtained from the IODP Site 339-U1385: reconstructed oxygen concentration and stable isotope measurements for the past 1.5 Ma; paired sample data focussed on the MIS 27-21 interval including measurements for oxygen concentration, stable isotopes, U/Ca, U/Mn, carbon isotope gradients for both C. wuellerstorfi-G. affinis and C. wuellerstorfi-Uvigerina peregrina, as well as Uvigerina spp. abundance; Ba/Al data; Core-top data for a pilot study transect through Shackleton Site stations; and Gaussian Interpolated data for the carbon isotope gradient between C. wuellerstorfi-G. affinis from this study combined with Iberian Margin Site MD95-2042 data of Hoogakker et al. (2015; doi:10.1038/ngeo2317) for the last 160 ka data.